AR Snakes and ladders game innovation to romote learning to live together in elementary schools - Ella Kusuma Wardani; Lisa Retnasari; Muhammad Alfarizqi Nizamuddin Ghiffari (International Journal of Mathematics and Sciences Education, 2025)
The declining acceptance of diversity among elementary school students poses a significant challenge, particularly in the context of rapid technological advancement in education. This study aims to: (1) develop a multicultural snakes and ladders learning media to promote learning to live together in elementary schools, and (2) evaluate its feasibility based on expert validation, teacher feedback, and student responses. The study employed a Research and Development (R&D) approach adapted from the ADDIE model. Data were collected through questionnaires and interviews and analyzed using descriptive quantitative techniques. The validation results indicated high feasibility, with subject matter experts rating the media at 88%, media experts at 77.3%, learning experts at 92%, and language experts at 86.6%, all categorized as very feasible. Teacher evaluations yielded a score of 86%, highlighting the media’s relevance, ease of use, and instructional clarity. Field testing involving 28 students at SD Negeri Giwangan demonstrated strong engagement and enthusiasm, achieving a score of 236 out of 270 (87.4%). These findings suggest that the multicultural snakes and ladders media is both technically and pedagogically feasible for fostering a harmonious learning environment and strengthening students’ understanding of Pancasila values within a culturally diverse context. However, this study was limited to small-scale trials; therefore, further research is recommended to examine the effectiveness of the media on learning outcomes in broader educational settings.